Prophylaxis Against Thromboembolic Events During Chemotherapy for Germ Cell Cancer - Meng, Xiaosong; Ahmed, Murtaza; Courtney, Kevin D.; Arafat, Waddah; Ibrahim, Ibrahim; Margulis, Vitaly; Nichols, Craig; Bagrodia, Aditya (Frontiers in Oncology, 2021)
Introduction Patients with advanced germ cell tumors (GCT) receiving cisplatin-based chemotherapy have high rates of thromboembolic events (TEE) which can negatively affect their overall survival. While primary TEE prophylaxis during chemotherapy may prevent these events, it is unclear which patients will benefit in this setting. Materials and Methods A review of PubMed/Medline was conducted in December 2020 and all pertinent articles were evaluated for relevancy and quality of data for inclusion in the review. Results Studies on patients receiving initial cisplatin-based chemotherapy for advanced GCT have reported up to a 19% rate of TEE. This high rate may be associated with multiple factors including retroperitoneal lymphadenopathy, advanced clinical stage, high risk Khorana scores and presence of a central line. Large phase III clinical trials have demonstrated the benefit of low-molecular-weight-heparin and direct oral anticoagulants for primary prophylaxis and against recurrent TEE. However, primary prophylaxis is currently underutilized with GCT patients starting chemotherapy. Conclusion Precise models to predict TEE risk and consideration of anticoagulation are difficult to develop owing to the relatively uncommon nature of GCT and lack of representation in primary TEE prophylaxis clinical trials. Despite these limitations, we believe that the benefits of prophylactic anticoagulation outweigh the risk of major bleeding in select GCT patients with higher risk of TEE. We have developed a simple algorithm to help guide TEE prophylaxis selection based on patient factors and route of chemotherapy administration. Given the high rate of TEE in GCT patients, we believe better utilization of primary prophylaxis in patient starting cisplatin-based chemotherapy will have clinical benefit.